Displacement of Morphological Characters of Barbodes gonionotus at Serpeng Cave Lake, Gunungkidul (Biodiversitas Journal of Biological Diversity, 2016)
Serpeng cave lake is located inside a cave that is isolated from any waters outside the cave, and the lake is located about 96 meters down under the ground surface. The isolated waters in the lake have also resulted in the isolation of the fishes from any other fish populations outside the cave. The objective of the study was to know how the displacement of morphological character occurred on a group of fish suspected belong to Barbodes gonionotus lived in Serpeng lake based on the observation of morphological characters of the fish. The Barbodes gonionotus from Kalisuci river and a well at Serpeng village was used as a comparison. The morphological characters observed were morphometric, meristic, color of scale, and number of vertebrae. The parameters of the water environment were also measured. The morphological characters from the three populations of fish were compared. The correlationcoefficient of the morphologic data was measured, and grouping analysis was also applied for data. There was not any obvious differences observed between fishes from Kalisuci river and well at Serpeng village, on the other hand, the differences were obviously observed for the fish from the lake compared to the fishes from the river and well. The differences were evident from all characters observed. The grouping analysis indicated that the fish population suspected to be Barbodes gonionotus from the lake was separated from the same species of the river and well, while the distinct features were not observed between both fishes from the river and well. Based on the basic charactersand observed morphological characters of Barbodes gonionotus suggest that the speciation of the fish to the subspecies taxonomic level has occurred.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: cave, geographic isolation, speciation, morphological character